2012
DOI: 10.1017/s0950268812000386
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serological markers and risk factors for bloodborne pathogens in Salvador, Bahia state, Brazil

Abstract: This study aimed to determine the prevalence of serological markers for HIV-1/2, HBV, HCV, Treponema cruzi and T. pallidum infections. The association of these infections with risk factors in a population from Salvador, Bahia, Brazil was also analysed. Of the 780 enrolled individuals, 545 (70%) were female and 235 (30%) were male. Seroprevalence of 0·8% (6/702), 1·3% (9/678), 1·5% (10/684), 3·5% (23/663) and 11·5% (77/668) for HIV-1/2, HBV, HCV, T. cruzi and T. pallidum infections, respectively, was observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Other authors have reported that sexual transmission seems to be an important HBV transmission route in areas of low endemicity 19,25,26 . In the current study, however, unprotected sex with multiple partners and previous STDs were not signifi cantly associated with HBV infection in the adjusted analysis, even though previous STDs were associated in the bivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Other authors have reported that sexual transmission seems to be an important HBV transmission route in areas of low endemicity 19,25,26 . In the current study, however, unprotected sex with multiple partners and previous STDs were not signifi cantly associated with HBV infection in the adjusted analysis, even though previous STDs were associated in the bivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Risk factors for HIV infection in the general population of Brazil have been evaluated in several studies . Sexual transmission is the cause of the majority of HIV/AIDS cases in Brazil, with almost half of infections attributable to unprotected sex among men who have sex with other men (MSM).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the risk of infection is higher. Each injection exposes the needle to blood and only one infected injection is needed to spread the infection among individuals who use shared instruments (1)(2)(3)(4). There is no problem if the needle is only used for one person.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of viral transmission is depends on the route of transmission, the type of virus, and the immune level of the exposed person (4,5,(8)(9)(10)(11)(12)(13). The most common routes of transmission for each virus includes: sexual intercourse (common for HBV, HIV and less common for HCV); sharing injecting equipment (efficient for HBV, HCV and HIV); skin puncture by bloodcontaminated sharp instruments (e. g., via a shared needle); and, the splashing of infected fluids to the mucous membranes (1,4,8,13). The overall risk of contracting HBV, HCV, and HIV, which can transmit by an infected patient to a healthcare worker (HCW ), are 30%, 3%, and 0.3%, respectively (2,4,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation